Moral imagination in Kaguru modes of thought - Beidelman, Thomas O. (Indiana University Press, 1986)
Within a conceptual framework taken from Wittgenstein, Beidelman shows how the Kaguru of Tanzania construct the scenarios of their social life, forming a consistent system that interprets and guides interaction.
free
Keywords: Kaguru (African people)